Visual Field Loss Progression after Macular Hole Surgery. (13th January 2010) - Tosi, Gian Marco; Martone, Gianluca; Balestrazzi, Angelo; Malandrini, Alex; Alegente, Marco; Pichierri, Patrizia
Abstract : Purpose . To report a patient who experienced visual field loss progression after vitrectomy for an idiopathic stage II macular hole. Methods . Case report. A 68-year-old woman, with no history of glaucoma or any neuroophthalmological diseases, underwent a vitrectomy for a macular hole. Results . The patient showed macular hole closure and a resulting central visual acuity of 20/20. However, two months after surgery, she developed an inferotemporal visual field defect. Moreover, seven months after surgery, the patient noticed an enlargement of the temporal blind area: a nearly complete temporal defect was confirmed on visual field testing. Conclusions . Although the beneficial results of successfully treated macular holes are unquestionable, this report raises the possibility that visual field defects following macular hole surgery may be progressive.